PENERAPAN ETIKA BISNIS DIERA DIGITALISASI: STUDI LIRETARUR - Fahmi Fadilla; Beni Wahyu Ariyudi; Sholahuddin Sahariawi; Alfin Nathanael; Agustiawan Agustiawan (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
The digital era has brought about major changes in the business world, creating challenges and opportunities that affect various aspects of a company's operations. The main challenges include the need to integrate modern technology with business ethics for the sake of the company's desires. This study discusses the role of accounting theory and business ethics in supporting business transformation in the digital era through a literature study. The results show that flexible accounting theory can help companies manage transactions, increase transparency, and reduce risks in the digital environment. On the other hand, business ethics plays a role in building trust, maintaining reputation, and protecting consumers and personal data. By integrating technology, ethical principles, and accounting theory, companies can create competitive and sustainable business strategies in the global market. This combination allows companies to face digital challenges while still prioritizing ethical values and desires.